efektivitas EFEKTIVITAS MEDIA AUDIO VISUAL DALAM MENINGKATKAN PENGETAHUAN AKSEPTOR NON MKJP TERHADAP KONTRASEPSI IUD DI PMB MUTIA VARINA: EFFECTIVENESS OF AUDIO-VISUAL MEDIA INENHANCING KNOWLEDGE OF IUD CONTRACEPTION AMONG NON-LTCM ACCEPTORS AT PMB MUTIA VARINA - Paquita Jafier Herrin (Jurnal Penelitian Keperawatan Kontemporer, 2026)
Background: The use of non-hormonal long-term contraceptive methods (IUDs) in Indonesia remains low, partly due to limited knowledge among Non-LTCM acceptors. This study aimed to evaluate the effectiveness of audio-visual media in improving IUD contraception knowledge. A pre-experimental one-group pretest–posttest design was applied to 37 respondents at PMB Mutia Varina, Pekanbaru, selected through purposive sampling. The instruments used were an educational video and a structured knowledge questionnaire. Pretest results showed that 51.4% of respondents had low knowledge, whereas after the intervention all respondents (100%) were categorized as having high knowledge. The mean score increased from 12.65 to 21.54. The Wilcoxon signed-rank test showed a significant difference with p=0.000 (<0.05). It can be concluded that audio-visual media is effective in enhancing knowledge of IUD contraception among Non-LTCM acceptors and is recommended as an alternative educational method in midwifery services.